Factors Influencing Indonesian Tourists’ Interest in Visiting South Korea - Marie, Andhalia Liza; Prasetio, Arton Briyan (Jurnal Penelitian Pariwisata, 2024)
The purpose of this research to measure the influence of film tourism and electronic word of mouth (e-WOM) on Indonesian tourists' intention to visit South Korea, as well as determine the role of destination image in mediating the influence of film tourism elements on interest in visiting South Korea. 140 respondents, who are fans of South Korean films or dramas but haven't experienced South Korea, engaged in the online survey. This research uses SEM-PLS for primary data processing. The results of the research show that South Korean tourism films have a positive and significant influence on the formation of the destination image of the country of Ginseng among Indonesian tourists. E-WOM does not have a positive and significant effect on Indonesian tourists' intentions to visit South Korea. The destination image of South Korea has a positive and significant impact on Indonesian tourists' intention to visit. Destination image is proven to significantly mediate the influence of film tourism on the desire of Indonesian tourists to visit South Korea. Destination image is proven to significantly mediate the influence of e-WOM on Indonesian tourists' desire to visit South Korea. Keywords: destination image, electronic word of mouth, film tourism, visit intention